Cover, Content, and Editorial Note from Borneo J Pharm Vol. 1 No. 1 May 2018 - Chief Editor of Borneo J Pharm (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. After a long wait for almost 12 years from the first stand, finally, the scientific journal of the Department of Pharmacy Universitas Muhammadiyah Palangkaraya can be published. This scientific journal we named Borneo Journal of Pharmacy (Borneo J Pharm), inspired by the rich treasures of traditional medicine from the Borneo island which further became the basis for the development of this periodical scientific publication. Borneo J Pharm published every 6 months (2 issues/year) every May and November. The aim of this journal is to publish high-quality articles dedicated to all aspects of the latest outstanding developments in the field but not limited to Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Natural Product Development, Clinical-Community Pharmacy, Management Pharmacy, and other Pharmacy aspects. It was first published online in May 2018 using Open Journal System (OJS) 3.1 platform with e-ISSN 2621-4814 by URL http://journal.umpalangkaraya.ac.id/index.php/bjop. This edition contains 12 articles consisting of Pharmacognosy-Phytochemistry, Natural Product Development, Clinical-Community Pharmacy, and Management Pharmacy topics. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. We hope that all parties, especially the contributors of the articles, could participate in the success of the publication in the next edition in November 2018. Wassalamu’alaikum Wr. Wb.